2015
DOI: 10.3892/etm.2015.2804
|View full text |Cite
|
Sign up to set email alerts
|

Association between colon diverticula and hemoglobin, triglyceride and uric acid levels

Abstract: Abstract. Colon diverticula cause bleeding and acute diverticulitis. The present study analyzed laboratory test variables, aiming to predict the presence of diverticula. Patient records from between April 2011 and March 2014 were analyzed retrospectively (1,520 patients) and a one-way analysis of variance was performed to analyze the association between the presence of diverticula and each variable. A χ 2 test was then used to assess the correlation between the prevalence of diverticula and the percentage of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that factors such as increasing age [ 6 ], male sex [ 7 ], and alcohol consumption [ 5 ] are correlated with colonic diverticulosis. Intense physical activity decreases the risk of colonic diverticulitis and colonic diverticular hemorrhage [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that factors such as increasing age [ 6 ], male sex [ 7 ], and alcohol consumption [ 5 ] are correlated with colonic diverticulosis. Intense physical activity decreases the risk of colonic diverticulitis and colonic diverticular hemorrhage [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from other studies revealed a correlation between serum UA levels, CVD, CKD, and stroke [ 26 ]. However, few studies [ 7 ] have assessed the association between serum UA levels and colonic diverticulosis. Several studies have shown that patients with hyperuricemia are at a higher risk of developing colonic diverticular hemorrhage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations